COVID-19 related knowledge, attitude and practices in a Southeastern city in Nigeria: The Baseline - Nchebe-Jah Raymond Iloanusi; Sorochi Iloanusi; Osaro Mgbere; Anthony Idowu Ajayi; Ekere J. Essien (Social Sciences and Humanities Open, 2023)
Although guidelines and recommendations for the prevention of COVID-19 are in place, it is vital to assess how well people know and practice them, as well as people's attitude towards these measures to inform robust interventions. This study examined COVID-19 related knowledge, attitude, and preventive practices. We conducted a cross-sectional survey of 140 adult residents of Onitsha, Anambra state in March 2020 before the state's index case and the mandatory lockdown. Descriptive and inferential statistics were used to describe COVID-19 KAP, information gaps and needs, and associations between KAP and demographic characteristics. About 60.7% of respondents had high COVID-19 knowledge, 56.4% had a good attitude towards COVID-19 management, and 53.6% adopted good COVID-19 prevention practices. Participants with bachelor/postgraduate degrees had higher than average COVID-19 knowledge (15.42 ± 0.57, p < 0.0001), attitude (1.11 ± 0.10, p < 0.0025), and prevention practice (5.02 ± 0.32, p < 0.0005) scores. Over half of the participants correctly identified virus as the cause of COVID-19 (60%, p < 0.01). About three-quarters of the participants (75%, p < 0.0001) indicated needing more information on COVID-19. A moderate proportion of our study population (53.6–60.7%) had good COVID-19 KAP. Our study findings can inform future COVID-19 program planning to ensure a more targeted and effective intervention strategy to prevent and control the disease spread among residents of Onitsha city.